Consideration of Meteorological Conditions when Determining the Navigational Water Depth over a Sandwave Field - Langhorne, D. N. (The International Hydrographic Review, 2015)
In a sandwave field in the Outer Thames Estuary, Great Britain, dune bed forms occur on the flanks and crests of the sandwaves. Studies of the dunes, as depicted by high-resolution sonar, show that the dunes are normally dominated by tidal flow conditions and that a relatively constant mean wave length (4.5 in) is maintained. In the event of adverse wreather when large surface waves occur in the area, the tidal dunes are replaced by dunes with a significantly shorter wave length (1.5 m to 1.7 m) . With the moderation of wave conditions the dunes progressively revert to their tidal equilibrium condition. If such redistribution of sediments can be shown to occur on the flanks of a sandwave, then similar or greater action is to he expected in the crestal area, probably affecting safe navigational depths.